Synthesis and Characterization of Methoxy-Substituted Salamo-Type Bisoximes Based on Bis(aminooxy)alkane and 3-Methoxy-2-hydroxybenzaldehyde - Ren1, Zong-Li; Gao2, Su-Xia; Zhang1, Yang; Wang1, Li; Dong1, Xiu-Yan (Asian Journal of Chemistry, 2014)
Four new methoxy-substituted Salamo-type bisoxime compounds 6,6'-dimethoxy-2,2'-[(propylene-1,3-diyldioxy)bis(nitrilo-methylidyne)]diphenol (H2L1), 6,6'-dimethoxy-2,2'-[(butylene-1,4-diyldioxy)bis(nitrilomethylidyne)]diphenol (H2L2), 6,6'-dimethoxy-2,2'-[(propane-1,5-diyldioxy)bis(nitrilome-thylidyne)]diphenol (HH2L3) and 6,6'-dimethoxy-2,2'-[(hexane-1,6-diyldioxy)bis(nitrilo-methylidyne)]diphenol (H2L4) have been synthesized through condensation reactions under hot ethanol medium, respectively and characterized by elemental analyses, IR, UV-visible and 1H NMR spectra.